(untitled) (LEGAL DIALOGICA, 2025)
This research aims to understand and analyze how the principles of justice and the principle of popular sovereignty relate to legislative candidates from political parties that are unable to meet the parliamentary threshold, as well as to determine and analyze how the representation of voters for legislative candidates from political parties that do not meet the parliamentary threshold will be in the 2024 general election. The research method used by the author is normative legal research, involving secondary data in the form of literature studies and journals related to the principles of justice and popular sovereignty as well as the parliamentary threshold in the 2024 elections. Based on the research findings, the author found that the principles of justice and popular sovereignty in political parties participating in the 2024 general election have not been fully implemented as they should be; justice, which is the people’s fundamental right regarding popular sovereignty, is obstructed by the rules of the parliamentary threshold applied, thus political parties are unable to fully represent the aspirations of the community. The study recommendations suggest that the House of Representatives, as the institution that designs and ratifies laws, should further examine the parliamentary threshold regulations that affect the increase in the number of votes that are wasted or not converted into seats in the House of Representatives, the parliamentary threshold that also limits sovereignty and is unfair to legislative candidates. Keywords: Justice, People’s Sovereignty, Parliamentary Threshold, Political Parties. Abstrak Penelitian ini bertujuan untuk mengetahui dan menganalisis bagaimana prinsip keadilan dan prinsip kedaulatan rakyat terhadap calon anggota legislatif pada partai politik yang tidak mampu memenuhi ambang batas parlemen, serta untuk mengetahui dan menganalisis bagaimana representasi keterwakilan pemilih calon anggota legislatif dari partai politik yang tidak memenuhi ambang batas parlemen pada pemilihan umum tahun 2024. Metode Penelitian yang penulis gunakan yaitu penelitian Hukum Normatif yang berupa perundang-undangan data sekunder yaitu studi kepustakaan dan jurnal yang berkaitan dengan prinsip keadilan dan kedaulatan rakyat serta ambang batas parlemen pada pemilu 2024. Berdasarkan hasil penelitian penulis menemukan bahwa prinsip keadilan dan kedaulatan rakyat pada partai politik peserta pemilihan umum tahun 2024 belum telah terlaksana sebagaimana mestinya, keadilan yang merupakan hak dasar rakyat atas kedaulatan rakyat tersebut terhalang oleh aturan ambang batas parlemen yang diterapkan, sehingga partai politik tidak mampu merepresentasikan secara menyeluruh aspirasi masyrakat. Rekomendasi penelitian menyarankan Dewan Perwakilan Rakyat sebagai lembaga perancang dan pengesahan Undang-undang harus mengkaji lebih lanjut terkait aturan ambang batas parlemen yang berpengaruh pada peningkatan jumlah suara yang terbuang atau tidak terkonfersi menjadai kursi pada Dewan Perwakilan Rakyat, Ambang batas parlemen yang juga membatasi kedaulatan serta berlaku tidak adil pada calon anggota legislatif.